Índice de clorofila no desenvolvimento de soja e milho e sua correlação com atributos químicos e físicos do solo e produtividade. - Rocha, Davi Marcondes (2013)
The Brazilian agriculture, propelled by the globalization of world s economy, needs to develop new technologies and studies that will increase yield and decrease the costs of production. This increase can be achieved through the management of adequate productive areas and must be cautious about its environmental impact, attempting to cause less impact and more production. Since nitrogen is one of the most useful agricultural inputs, it is important the development of researches aiming local application and evaluating the influence of this and other nutrients on the agricultural production. Determining the amount of chlorophyll is a method that has been being utilized to predict the necessity of nitrogen fertilization in various cultures. This research had the objective of evaluating spatial dependence and creating thematic maps referring to the index of chlorophyll in comparison with the growing of soybean and corn culture for correlation analysis with chemical and physical attributes and yield. It was used a portable device to measure the index of chlorophyll (non-destructive, inexpensive and fast, when compared to laboratory process). It were applied techniques of spatial dependence analysis on data constructing thematic maps through interpolation by kriging. All chemical and physical soil properties showed spatial dependence, allowing site-specific management of these attributes. The yield presented spatial correlation with chemical and physical soil properties and spatial correlation between chlorophyll and productivity was proved significant, mostly in vegetative stages.